1978
DOI: 10.1002/chin.197820131
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: ALKYLATION OF SOME CYANO DERIVATIVES OF BENZIMIDAZOLES

Abstract: Die Alkylierung der Benzimidazole (I) mit Benzylchlorid (Va) liefert die Seitenketten‐Substitutionsprodukte (II); die Alkylierung des Benzimidazols (III) ‐ als Tautomerengemisch mit der Form (IV) vorliegend ‐ mit den Reagenzien (V) bzw. (VI) gibt dagegen die Derivate (VIIa) [mit l mol (Va)] bzw. (VIIb) [mit 2 mol (Va)], (VIIc) bzw. (VIId).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Second, the IR spectra showed that cyano group is represented by an absorption band at 2225–2240 cm −1 , which is in excellent agreement with the structure ―N(R)―C≡N. The alkylation of endo‐cyclic nitrogen atom should lead to the formation of cyanoimino =N―C≡N group, in which an absorption band of cyano group is given at 2150–2190 cm −1 .…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…Second, the IR spectra showed that cyano group is represented by an absorption band at 2225–2240 cm −1 , which is in excellent agreement with the structure ―N(R)―C≡N. The alkylation of endo‐cyclic nitrogen atom should lead to the formation of cyanoimino =N―C≡N group, in which an absorption band of cyano group is given at 2150–2190 cm −1 .…”
Section: Resultssupporting
confidence: 52%
“…For cyanamide 1 , isomer Ib is more energetically preferable, but the difference in the energies of isomers Ia and Ib is small. For cyanamide 2 , the isomers IIa and IIc are energetically favorable, and the formation of alkylated carbodiimide derivatives Ic and IIc has not been reported for the studied reaction . Thus, we can predict that the reaction with 1 in thermodynamic conditions can produce both Ia and Ib , with Ib being slightly more favorable, while the only product of reaction with 2 will be IIa .…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Unlike the 2-aminobenzimidazole that in the reaction with acylmethylbromides [11,12] and with esters of haloacetic acids [13] even in a neutral medium and under mild conditions (acetone, room temperature [12]) formed mixtures of N-acyl-(alkoxycarbonyl)methyl-substituted and of the corresponding N,N'-disubstituted 2-aminobenzimidazoles, the alkylation of 2-hydroxyalkylaminobenzimidazoles Ia and Ib, with haloketones IIb-IIe proceeded under more stringent conditions and resulted only in monosubstituted III and IV.…”
mentioning
confidence: 98%